When I do these questions, these are my answers... Could someone please tell me what i am doing wrong..?
(x-2)(x-2)
(x-2)(x+3)
(x-2)
(x+3)
((2)-2)
((2+3)
0
5
= 0
correct x
x
= 0? DNE?
I still don't fully understand the concept with this one..
if , then if , then (x-1)(x^2+2x+1)
(x-1)
Wrong, This is the formula Try to do it again.
x^2-2x+1
(1)^2 - 2(1) + 1
1-2+1
= 0
(x+5)(x-1)
(x-1)(x-1)
No No No, Try to factor the denominator again. (x+5)
(x-1)
((1)+5)
((1)-1)
6
0
= DNE
(x-2)(x^2+4x+4) Same mistake, The formula is Try to do it again.
12(x-2)
(x^2+4x+4)
12
((2)^2 + 4(2) + 4
12
4+8+4
12
=4/3